PENGARUH PHONOLOGICAL AWARENESSTERHADAP KEMAMPUAN PENYELESAIAN SOAL CERITA MATEMATIKA SISWA SEKOLAH DASAR - Ratnengsih, Een (PEDAGOGIA, 2015)
This research entitled "The Effect of phonological awareness for Problem Resolution Capability in Elementary School Math Stories". The purpose of this study was to determine the effect of phonological awareness component (semantic and syntactic) the ability of the completion of a story about math at the Grade 1 Elementary School. The achieve the research objectives, this research is using the exposure facto quantitative approach. The data collection in this study using a test technique with one retrieval, which tests math story problem resolution skills and phonological awareness skills test. The data was analyzed using path analysis. The samples in this study were 96 students of grade 1 elementary school in the District Antapani Bandung.The results show that phonological awareness components (semantics and syntax) and the combined partial both have a significant effect on the ability of the settlement effect story about the math of the completion of a story about math at theElementary School (reading comprehension, mathematic computation, and comprehension).Keywords : Phonological awareness,kemampuan penyelesaian soal cerita matematika